A reduced-order generalized proportional integral observer-based resonant super-twisting sliding mode control for grid-connected power converters - Lu, Jinghang (2022)
This article presents a reduced-order generalized proportional-integral observer based resonant super-twisting sliding mode controller (RST-SMC) for the three-phase ac-dc converters. On the contrary to utilizing the proportional-integral controller in regulating the dc-link voltage, which may cause large undershoot/overshoot under the disturbance, the proposed voltage control strategy for the dc-link has high disturbance rejection ability and the settling time has been greatly reduced. In addition, the proposed RST-SMC in the current control loop not only preserve the merits of the sliding mode controller but also achieve the current tracking without steady-state error in the stationary α - β frame. The effectiveness of the proposed method has been verified by a lab-constructed experimental prototype.